STRATEGI MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X DI SMAN 8 MALANG PADA MASA PANDEMI COVID-19 - Anisa Tri Ahbatul Aini; Muhammad Hanif; Eko Setiawan (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Learning during the Covid-19 period certainly requires adjustments in the implementation of project-based learning. The condition of the Covid-19 pandemic has forced teachers and students to carry out distance learning which applies to all levels of education. Based on the results of interviews with the Principal, PAI teachers and direct observations made by researchers while carrying out Field Experience Practice (PPL) assignments for 40 days at SMAN 8 Malang or commonly called SMARIHASTA. The approach used in this study is a qualitative approach which in this qualitative study the author went himself to research and obtain data from resource persons about how the teacher's strategy in planning, implementing and evaluating the project based learning model strategy in learning Islamic religious education at SMAN 8 Malang. In planning the Project Based Learning strategy in learning Islamic religious education at SMAN 8 Malang, researchers still need improvements. Judging from the implementation of the Project Based Learning model in learning Islamic Religious Education at SMAN 8 Malang requires a process which cannot be separated from time indicators, applications used, teaching materials, and methods and evaluations.